Multiplex PCR-based next generation sequencing as a novel, targeted and accurate molecular approach for periprosthetic joint infection diagnosis - Huang, Changyu; Huang, Ying; Wang, Ziwen; Lin, Yiming; Li, Yongbin; Chen, Yang; Chen, Xiaoqing; Zhang, Chaofan; Li, Wenbo; Zhang, Wenming; Fang, Xinyu; Huang, Zida (Frontiers in Microbiology, 2023)
Periprosthetic joint infection (PJI) diagnosis remains challenging, and the identification of the causative microorganism is, by far, the most important aspect. Here, we use multiple PCR-based targeted next-generation sequencing (tNGS) to detect pathogens in PJI. Specific sequences of 298 pathogens and 86 drug resistance genes were included in the panel of PCR. PJI was diagnosed according to the Musculoskeletal Infection Society (MSIS) criteria. The microorganisms were detected by culture, metagenomic next-generation sequencing (mNGS) and tNGS to compare the diagnostic effectiveness of the three methods for PJI and to compare their consistency in detecting microorganisms. Drug resistance genes were detected using tNGS. The costs and turnaround times of mNGS and tNGS were compared. Finally, 43 patients with PJI, 21 patients without PJI, and 10 negative control cases were included. The culture, tNGS, and mNGS sensitivities for PJI diagnosis were 74.4%, 88.4%, and 93.0%, respectively, with no significant differences. The specificities were 90.5%, 95.2%, and 95.2%, respectively, with no significant differences. tNGS detected drug resistance genes in 37.5% of culture-positive PJIs. tNGS was superior to mNGS for turnaround time (14.5 h vs. 28 h) and cost (150 vs. 260). In conclusion, as a multiplex PCR based NGS technology, tNGS can effectively detect microorganisms within the panel, and provide similar diagnostic value as that of commonly used indicators, moreover, it can provide information on drug resistance. And tNGS is superior to mNGS in terms of cost and turnaround time. A multidisciplinary, multi-technology based algorithm to diagnose PJI is appropriate.